FEEDFORWARD ALGORITHMS WITH SIMPLIFIED PLANT MODEL FOR ACTIVE NOISE CONTROL - Pawelczyk, M (Journal of sound and vibration, 2002)
Most feedforward active noise control (ANC) algorithms require models of electro-acoustic paths. To obtain satisfactory attenuation and keep the system stable these models have to represent the plant well. This, according to the literature, requires estimation of many, often hundreds of coefficients. Then, control filters also have very large, comparable structures. Such an approach reveals significant drawbacks if paths of the plant are subject to change. Estimation of so many plant models and control filter coefficients is very slow and time consuming. Therefore, the speed of adaptation is substantially reduced. This can be accepted in some unmoveable plants like acoustic ducts. However, there are many other plants, e.g., active personal hearing protection devices, in which rapid reaction is also of utmost interest not to annoy the user. In this paper, an alternative approach is proposed that does not need precise models except an estimate of the discrete time delay of the plant. However, according to the literature this leads to a relatively narrow attenuation band, which is confirmed for classical control structures like finite and infinite impulse response filters. This becomes a premise to design a new control algorithm. First, the so-called phase shifters (in two versions) are designed. They enable to control narrowband noise on comparable levels with at least an order less parameters than the filters mentioned above. To control broadband noise, the idea of phase shifter banks is then put forward. In turn, to extend the attenuation band conversion of sampling frequency is adopted to noise control problems. Finally, the algorithm combining advantages of phase shifter banks and conversion of sampling frequency allows controlling of any noise over any frequency band, with limits imposed only by the signal processor available and pass-band of the secondary source. Although this algorithm is designed generally and can be applied to any ANC plant, for laboratory experiments an active personal hearing protection device is used.